PENGELOMPOKAN SAYURAN BERDASARKAN KEMIRIPAN KANDUNGAN GIZI - DEWI, AYU SANDRA TIARA; SUCIPTAWATI, NI LUH PUTU; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2018)
One of the either of health maintain is trough the food consumption pattern that fulfill nutrient content. Vegetables are needed to body as source of vitamin, mineral and fiber in gaining healthy food pattern as a recommended guidance of nutrient balancing for optimal health. This research is aimed to determine several type of vegetables that have similarity of nutrient content and types of nutrient content which characterized of each vegetables grup. The method is biplot analysis. Biplot analysis can show the type of vegetables and type of nutrient content simultaneously in a two-dimensional plot. From this plot, the information about vegetables that have similarity of nutrient content and type of nutrient content which characterized of each vegetables group. This research used 37 type of vegetable as an observation object and type of nutrient content observed is 13. The result of this analysis is obtained 7 vegetables group with different characteristic changes.